The human cathelicidin LL-37 has antiviral activity against respiratory syncytial virus. - Silke M Currie; Emily Gwyer Findlay; Brian J McHugh; Annie Mackellar; Tian Man; Derek Macmillan; Hongwei Wang; Paul M Fitch; Jürgen Schwarze; Donald J Davidson (PLoS ONE)
Respiratory syncytial virus is a leading cause of lower respiratory tract illness among infants, the elderly and immunocompromised individuals. Currently, there is no effective vaccine or disease modifying treatment available and novel interventions are urgently required. Cathelicidins are cationic host defence peptides expressed in the inflamed lung, with key roles in innate host defence against infection. We demonstrate that the human cathelicidin LL-37 has effective antiviral activity against RSV in vitro, retained by a truncated central peptide fragment. LL-37 prevented virus-induced cell death in epithelial cultures, significantly inhibited the production of new infectious particles and diminished the spread of infection, with antiviral effects directed both against the viral particles and the epithelial cells. LL-37 may represent an important targetable component of innate host defence against RSV infection. Prophylactic modulation of LL-37 expression and/or use of synthetic analogues post-infection may represent future novel strategies against RSV infection.